2019
DOI: 10.3389/fnins.2019.00463
|View full text |Cite
|
Sign up to set email alerts
|

S100 Proteins in Alzheimer’s Disease

Abstract: S100 proteins are calcium-binding proteins that regulate several processes associated with Alzheimer’s disease (AD) but whose contribution and direct involvement in disease pathophysiology remains to be fully established. Due to neuroinflammation in AD patients, the levels of several S100 proteins are increased in the brain and some S100s play roles related to the processing of the amyloid precursor protein, regulation of amyloid beta peptide (Aβ) levels and Tau phosphorylation. S100 proteins are found associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(121 citation statements)
references
References 125 publications
5
113
0
3
Order By: Relevance
“…Evaluated levels of several S100 proteins could also be observed in the brain of Alzheimer's patients. These S100 family members, namely S100A1, S100A6, S100A7, S100A8, S100A9, S100A12, and S100B, seem to be involved in the progression of Alzheimer's disease (AD), including the formation of amyloid aggregates, and could thereby be promising regarding new therapeutic approaches [66]. S100A1 seems to be an essential factor concerning cardiological diseases since it is involved in the contractile performance of cardiomyocytes [36,37].…”
Section: Clinical Relevance Of S100 Proteinsmentioning
confidence: 99%
“…Evaluated levels of several S100 proteins could also be observed in the brain of Alzheimer's patients. These S100 family members, namely S100A1, S100A6, S100A7, S100A8, S100A9, S100A12, and S100B, seem to be involved in the progression of Alzheimer's disease (AD), including the formation of amyloid aggregates, and could thereby be promising regarding new therapeutic approaches [66]. S100A1 seems to be an essential factor concerning cardiological diseases since it is involved in the contractile performance of cardiomyocytes [36,37].…”
Section: Clinical Relevance Of S100 Proteinsmentioning
confidence: 99%
“…Importantly, human brains showed a similar pattern of expression [5355]. S100B acts as a pro-inflammatory cytokine, and several studies reported high levels of S100B in AD patients [56] and mouse models of AD [56]. Similarly, s100b expression in the zebrafish brain region was elevated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the S100 family of proteins have been investigated for their role in AD, based on their ability to influence the Aβ aggregation pathway and its cellular receptors. While evidence shows that their function depends on the stage of pathology and related levels of Aβ and S100 proteins, it is possible that the S100 family could function as molecular chaperones to suppress oligomer toxicity through several mechanisms [ 169 , 170 ]. Development of chaperone-targeted therapeutics is limited by their stability, oral bioavailability, and blood–brain barrier permeability.…”
Section: Targeting Misfolded Protein Oligomers By Potentiating Thementioning
confidence: 99%